Progress report on functional literacy. - Philippines (Republic) Presidential Assistant on Community Development; Philippines (Republic). Bureau of Public Schools; Division of Adult Education ([Manila s.n.)
Quarterly.
Keywords: Education of adults; Education -- Philippines